Isolation of lignans glycosides from Alibertia sessilis (Vell.) K. Schum. (Rubiaceae) by preparative high-performance liquid chromatography - Da Silva, V. C. [UNESP]; Silvab, G. H.; Da S Bolzani, V.; Lopes, Márcia Nasser [UNESP] (FapUNIFESP (SciELO), 2006)
Enantiomeric aglycone lignans contained in a mixture were separated from a fraction of the extract of the stems of Alibertia sessilis (Vell.) K. Schum. (Rubiaceae) by preparative high-performance liquid chromatography. An efficient and fast separation can be achieved with methanol-water (30:70, v/v). Their structures were identified as (+)-lyoniresinol 3α-O-β-glucopyranoside and (-)-lyoniresinol 3α-O-β-glucopyranoside, being reported for the first time in Rubiaceae.
Keywords: Alibertia sessilis; Enantiomeric aglycone lignans; HPLC; Rubiaceae